Automotive Chassis Frame Structural Analysis and Design Modification for Weight Reduction - N. FRANCIS; RAO, S. KAMALESH (International Journal of Psychosocial Rehabilitation, 2020)
Automobile chassis usually refers to the lower body of the vehicle and it is an important part of an automobile. The chassis serves as a frame work for supporting the body and different parts of the automobile. Also, it should be rigid enough to withstand the shock, twist, vibration and other stresses. Along with strength, an important consideration in chassis design is to have adequate bending stiffness for better handling characteristics. So, maximum stress, maximum equilateral stress and deflection are important criteria for the design of the chassis. In this present study work is performed towards the optimization of the automotive chassis with constraints of equivalent stress and deflection of chassis. Sensitivity analysis is carried out for thickness and height by keeping width constant. Structural systems like the chassis can be easily analyzed using the finite element techniques. So a proper finite element model of the chassis developed. FEA is done on the modeled chassis using the ANSYS Workbench. Initially structural analysis was carried out for old and optimized design. Optimized chassis have lower stresses and deflections. Modal analysis is carried out to find natural frequencies and mode shapes of the existing as well as modified chassis. It is observed that all the natural frequencies of optimized chassis were below 100 Hz, varying from 14 Hz to 27 Hz for first three mode shapes. Almost all of the truck chassis designs were based on these frequency ranges to avoid the resonance during the operating condition.